TOLERANCE IN DIVERSITY : INTEGRATING THE TRILOGI UKHUWAH INTO MULTICULTURAL EDUCATION AT SMP NEGERI 3 AMBULU JEMBER - Muhammad Shobirin (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2025)
Indonesia's diversity in ethnicity, culture, and religion is valuable asset, but it can be a menace if it is not manag?d prop?rly. The integration of multicultural education and ukhuwah trilogy concept of brotherhood can be a very significant foundation in overcoming menace of diversity. The purpose ofthis research is to examine th? crucial significance of multícultural educátion, integrated through the inculcation of trilogy ukhuwah values, in fostering tolerance at SMP Negeri 3 Ambulu, Jember. This school is uniquely situated in a village predominantly Christian, although the majority of its students are Muslim. Using a qualitative approach, this study delves into a case study to achieve a comprehensive understanding and holistic understanding of the pedagogical strategies and tangible impacts of integrating Ukhuwah values in shaping a culture of tolerance within a heterogeneous environment. The data wer? collected through observatíon, in depth intervi?w, and documentation studíes. Reduction, presentation, and conclusion drawing served as the data analysis techniques. The research findings proved that the school effectively inculcates trilogy Ukhuwah values into its intracurricular activities, further reinforced by cocurricular and extracurricular programs, thereby creating a tolerant climate amidst differences. It was found that, this strategy successfully cultivated a strong attitude of tolerance among students, manifested in their acceptance of differences, interfaith empathy, harmonious interactions, and strengthened national pride. This study concluded that, the integration of trilogy ukhuwah in multcultural ?ducation can be effective model for building inclusive and tolerant school communities amidst diversity.